Sports Day in Canada: examining the benefits for event organizers (2010–2013). Issue 2 (4th March 2017) - Luciani, Alicia; White, Lauren; Berry, Tanya R.; Deshpande, Sameer; Latimer-Cheung, Amy E.; O'Reilly, Norm; Spence, John C.; Rhodes, Ryan E.; Tremblay, Mark S.; Faulkner, Guy
Abstract : The impact of large-scale, 'mass' community-based sport, and physical activity (PA) events on population PA has yet to be established. The enhancement of organizational capacity to support health promotion initiatives is one mechanism through which such events may be helpful. Sports Day in Canada (SDIC) is an annual, nation-wide event celebrating the role of sport within communities and promoting sport participation. Beginning in 2010, thousands of Canadian sport and PA organizations have created SDIC events each year. The objective of this study was to examine the types of organizations who participate in SDIC and to determine if and how these organizations benefit from hosting an event. Online surveys of event organizers (2010 to 2013 SDIC) were conducted. Descriptive analyses identified organization and event characteristics, and one-way ANOVAs across time assessed event organizers' perceptions related to their overall satisfaction, benefits obtained, and challenges faced while participating in SDIC. Findings showed that organizations were mainly from the provinces of Ontario, British Columbia, and Quebec, worked with children and youth, and registered an event that was a tournament or school based. There was a significant increase in overall satisfaction [ F (3, 996) = 27.26, p  < .001] and benefits obtained [ F (3, 1000) = 18.36, p  < .001] across all four years of SDIC. One main benefit reported by organizations was an increased awareness and interest among community members in sport program(s) offered by their organization. Mass events like SDIC may help enhance organizational capacity to deliver health promotion initiatives including sport and PA programming.